Democracy and Social Cleavage in India - Nath, Suman.
1 online resource (154 pages).
Keywords: This book explores the emergence of identity politics and violence at the forefront of political life in an Indian state. Through a close reading of everyday politics in West Bengal, India, which until recently boasted of the longest-serving elected communist government in the world, the volume presents unique observations on Indian politics and its trajectories. One of the first ethnographic studies of religious polarisation and its interface with politics in West Bengal, this book: Offers a fresh perspective, both theoretically and empirically, by using longitudinal, multi-site ethnography, to explain the mechanisms by which identity issues have re-emerged; Studies key policy changes, political practices, and series of invented traditions during periods of political transition; Examines intricate details of the micro-dynamics of the formulation and expansion of Hindu and Islamic fundamentalism and their political counterparts, which carry a capacity to push away secular, democratic forces from the existing political spectrum; Sheds light on the mechanisms of riots, its design, organisational bases, and mechanisms of spread; Includes key observations from the 2021 elections in the state. The volume will be of great interest to scholars and researchers of political science, social and cultural anthropology, sociology, and South Asian studies.